A Rare Case of Primary Pulmonary Anaplastic Large Cell Lymphoma - Carvalho, Joana (Eur J Case Rep Intern Med, 2019)
Non-Hodgkin lymphomas are rare causes of primary lung neoplasms and most are B-cell in origin. Anaplastic large cell lymphoma is an exceedingly rare type of primary pulmonary lymphoma, with an aggressive clinical course. We present the case of an 85-year old male patient who attended our Emergency Department complaining of respiratory and constitutional symptoms, and who was found to have a bronchial mass causing subtotal atelectasis of the left lung. Histological examination showed an anaplastic large cell lymphoma and further investigation revealed that it was limited to the lung. To our knowledge, very few similar cases have been reported in the literature. LEARNING POINTS: Non-Hodgkin lymphomas are rare causes of pulmonary lung neoplasms, with the majority of cases being marginal zone B-cell lymphoma of mucosa-associated lymphoid tissue or diffuse large B-cell lymphoma. Anaplastic large cell lymphoma (ALCL) usually involves the lymph nodes, skin and soft tissue. It follows an aggressive clinical course and constitutional symptoms are frequent at presentation. Lung involvement may occur as a result of dissemination in up to 12% of cases. Primary ALCL of the lung is extremely rare. Anaplastic lymphoma kinase (ALK) expression is an important prognostic factor, with ALK+ ALCL patients experiencing better outcomes. Adverse prognostic factors also include advanced age, serum lactate dehydrogenase levels and early relapse after therapy.